To solve the equation \( 2x - 5 = 3(4x + 5) \), you can follow these steps in order:
-
Distribute the right side: Apply the distributive property to the right side of the equation. \[ 3(4x + 5) = 12x + 15 \]
-
Rewrite the equation: Substitute the distributed expression back into the equation. \[ 2x - 5 = 12x + 15 \]
-
Isolate the variable terms: Move all terms containing \( x \) to one side of the equation and constant terms to the other side. You can subtract \( 2x \) from both sides: \[ -5 = 12x - 2x + 15 \] Simplifying this gives: \[ -5 = 10x + 15 \]
-
Move constants to one side: Subtract 15 from both sides to isolate the term with \( x \): \[ -5 - 15 = 10x \] This simplifies to: \[ -20 = 10x \]
-
Solve for \( x \): Divide both sides by 10 to find \( x \): \[ x = \frac{-20}{10} = -2 \]
-
Check your solution: Substitute \( x = -2 \) back into the original equation to verify it is correct.
So, the ordered steps are:
- Distribute the right side.
- Rewrite the equation.
- Isolate the variable terms.
- Move constants to one side.
- Solve for \( x \).
- Check your solution.